Information nation : seven keys to information management compliance - Kahn, Randolph (Wiley Pub., 2009)
"This fully updated edition demonstrates how businesses can succeed in creating a new culture of information management compliance (IMC) by incorporating an IMC philosophy into a corporate governance structure. Expert advice and insight reveals the proven methodology that adopts the principles, controls, and discipline upon which many corporate compliance programs are built and explains how to apply this methodology to develop and implement IMC programs that anticipate problems and take advantage of opportunities. Plus, you?ll learn how to measure information management compliance through the use of auditing and monitoring, following the proper delegation of program roles and components, and creating a culture of information management awareness"--Resource description page